2022
DOI: 10.3389/fspor.2022.892046
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Self-Talk Assists Basketball Free Throw Performance Under Conditions of Physical Exertion

Abstract: The purpose of the present study was to examine the effects of a strategic self-talk intervention on basketball free throw performance under conditions of physical exertion. Forty-one male basketball players (Mage = 23.19 years) participated in the study. Following a baseline assessment, a 3-week intervention was implemented. During this period participants of the two groups practiced the same number of free throws in their training sessions; participants of the experimental group practiced using self-talk and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Self-talk adalah keterampilan mental umum yang menyebabkan kecemasan karena self-talk adalah pernyataan yang dirancang untuk menenangkan diri. Para peneliti telah menunjukkan bahwa Nindiya Syafawani, Alit Rahmat, & Carsiwan Efektivitas penggunaan self-talk dalam pembelajaran penjas bagi siswa 843 self-talk pada olahraga dapat memengaruhi keterampilan dan kinerja dalam pertandingan (Galanis et al, 2022;Hidayat et al, 2023;Pop et al, 2021;Zourbanos et al, 2016). Stabilitas performa saat bermain merupakan salah satu faktor yang dipengaruhi oleh self-talk (Rammehar, 2021).…”
Section: Pendahuluanunclassified
“…Self-talk adalah keterampilan mental umum yang menyebabkan kecemasan karena self-talk adalah pernyataan yang dirancang untuk menenangkan diri. Para peneliti telah menunjukkan bahwa Nindiya Syafawani, Alit Rahmat, & Carsiwan Efektivitas penggunaan self-talk dalam pembelajaran penjas bagi siswa 843 self-talk pada olahraga dapat memengaruhi keterampilan dan kinerja dalam pertandingan (Galanis et al, 2022;Hidayat et al, 2023;Pop et al, 2021;Zourbanos et al, 2016). Stabilitas performa saat bermain merupakan salah satu faktor yang dipengaruhi oleh self-talk (Rammehar, 2021).…”
Section: Pendahuluanunclassified
“…Long taboo in the world of sports, mental health issues are now progressively being discussed, and psychologists and mind trainers are entering the Indian sporting community. The provision of sport psychology services utilises mental techniques for the improvement of performance and the development of mental skills, which occupy a significant portion of the sport psychology knowledge base [1]. As a society, we have come a long way in removing the stigma attached to mental health.…”
Section: Introductionmentioning
confidence: 99%
“…They also concluded that instructional self-talk can be a technique for beginner volleyball players. On the other hand, self-talk (internal conversation, interpersonal communication, inner or hidden speech, and selfcommunication) is one of the most common and reliable strategies for athletes to improve sports performance (Galanis et al, 2022). Previous research shows that the use of words or phrases helps athletes to pay attention, learn, learn, correct mistakes, develop competition plans, change or quite bad habits, create and change emotions and mood, think positively, strengthen expectations, create and increase self-esteem, motivation and achieving high levels of performance (Weinberg & Gould, 2011).…”
Section: Introductionmentioning
confidence: 99%